Genetic architecture of left ventricular noncompaction in adults - Ross, Samantha Barratt; Singer, Emma S.; Driscoll, Elizabeth; Nowak, Natalie; Yeates, Laura; Puranik, Rajesh; Sy, Raymond W.; Rajagopalan, Sulekha; Barratt, Alexandra; Ingles, Jodie; Bagnall, Richard D.; Semsarian, Christopher (Human genome variation, 2020)
The genetic etiology and heritability of left ventricular noncompaction (LVNC) in adults is unclear. This study sought to assess the value of genetic testing in adults with LVNC. Adults diagnosed with LVNC while undergoing screening in the context of a family history of cardiomyopathy were excluded. Clinical data for 35 unrelated patients diagnosed with LVNC at ≥18 years of age were retrospectively analyzed. Left ventricular (LV) dysfunction, electrocardiogram (ECG) abnormalities, cardiac malformations or syndromic features were identified in 25 patients; 10 patients had isolated LVNC in the absence of cardiac dysfunction or syndromic features. Exome sequencing was performed, and analysis using commercial panels targeted 193 nuclear and mitochondrial genes. Nucleotide variants in coding regions or in intron-exon boundaries with predicted impacts on splicing were assessed. Fifty-four rare variants were identified in 35 nuclear genes. Across all 35 LVNC patients, the clinically meaningful genetic diagnostic yield was 9% (3/35), with heterozygous likely pathogenic or pathogenic variants identified in the NKX2-5 and TBX5 genes encoding cardiac transcription factors. No pathogenic variants were identified in patients with isolated LVNC in the absence of cardiac dysfunction or syndromic features. In conclusion, the diagnostic yield of genetic testing in adult index patients with LVNC is low. Genetic testing is most beneficial in LVNC associated with other cardiac and syndromic features, in which it can facilitate correct diagnoses, and least useful in adults with only isolated LVNC without a family history. Cardiac transcription factors are important in the development of LVNC and should be included in genetic testing panels. Cardiomyopathy: Genetic testing largely unhelpful for rare heart disease Genetic testing is of limited use for diagnosing a rare heart muscle disorder called left ventricular non-compaction (LVNC), a structural abnormality of the lower left chamber of the heart in which the muscular wall appears soft and spongy rather than smooth and compacted. A team led by Christopher Semsarian from the University of Sydney, Australia, carried out a a retrospective analysis of genetic data from 35 patients diagnosed with LVNC but with no family history of the disease. They identified only three likely pathogenic gene variants, all in known heart regulatory genes and all in individuals with symptoms of cardiac dysfunction. The researchers conclude that genetic testing can facilitate a correct diagnosis of LVNC in patients showing signs of heart problems, but is largely unhelpful for those without symptoms and no family history.